Understanding and addressing bias in neonatal drug screening practices - Megan Kalata; Alexandra Van Cleave; Lillian Eason; Mary Kate Eiden; Amrita Purkayastha; Sun Young Guwn; Meghan Fries; Lauren Seger; Emily Callahan (Journal of Neonatal-Perinatal Medicine, 2026)
Background Urine drug screening (UDS) is commonly utilized to identify substance use during pregnancy and facilitate timely interventions aimed at mitigating adverse parental and neonatal outcomes. Current literature has demonstrated that UDS among pregnant patients is not uniformly applied across populations but less is known about screening practices among neonates. This study aimed to evaluate the demographics, clinical indications, documentation and disclosure practices, and outcomes associated with neonatal drug screening. Methods A retrospective chart review was completed for neonates at one academic institution whose birthing parent had undergone UDS. Statistical methods to analyze this data included t-tests, calculated percentages, and chi square analysis to compare whether the independent variables evaluated affected screening decisions. Results Of 651 neonates of parents who completed a UDS during their pregnancy, 273 (42.5%) screens were positive. Amphetamine (36.8%) and cannabinoid (38.6%) accounted for the majority of positive substances. Neonatal race and ethnicity data showed that the overall racial distribution of neonatal drug screens obtained was proportional to the racial representation in the study’s population. However, the proportion of patients screened in the study does not reflect the proportion of patients within each race and ethnicity found among the birthing population. The majority (97.8%) of drug screens obtained did not include documentation of parental consent. Conclusions Systemic changes need to be made to ensure equitable screening protocols exist for neonatal drug screens as well as ensure parental consent and knowledge of screening results is documented.